Inorganic Adsorption on Thermal Response and Wear Properties of Nanosilicon Nitride-Developed AA6061 Alloy Nanocomposite. (25th January 2023) - Anjalin, F. Mary; Krishnan, A. Mohana; Arunkumar, G.; Raju, K.; Vivekanandan, M.; Somasundaram, S.; Thirugnanasambandham, T.; Ramaraj, Elangomathavan
Abstract : Inorganic-based ceramic reinforcements are promising superior thermal behaviour and are lightweight and developed with aluminium alloy matrix for automobile applications. The AA6061 alloy nanocomposite containing 0 wt%, 4 wt%, 8 wt%, and 12 wt% of silicon nitride nanoparticles(50 nm) was synthesized by stir cast. The influences of thermal adsorption on silicon nitride (nano) additions, density, thermal response, hardness, and wear characteristics of AA6061 matrix nanocomposites are studied. Based on the rule of mixture, the density of nanocomposites is evaluated. The differential thermal and thermogravimetric analysis techniques are used to find the thermal response nanocomposite. The differential scanning calorimeter is used to find the heat flow between 400°C and 700°C. The micro Vickers hardness and wear characteristics of AA6061 nanocomposite were experimentally investigated by ASTM E384 and ASTM G99-05 standards. The adsorption of inorganic nanosilicon nitride particles (12 wt%) in AA6061 alloy showed a decreased mass loss with increased temperatures 0° to 700°C. The differential thermal analysis of nanocomposite reveals the transformation of solid-to-liquid phase under high temperature (528°C).